Chlorhexidine arrests subclinical degradation of dentin hybrid layers in vivo - Hebling, J.; Pashley, D. H.; Tjäderhane, L.; Tay, F. R. (SAGE Publications, 2005)
The recent paradigm that endogenous collagenolytic and gelatinolytic activities derived from acid-etched dentin result in degradation of hybrid layers requires in vivo validation. This study tested the null hypothesis that there is no difference between the degradation of dentin bonded with an etch-and-rinse adhesive and that in conjunction with chlorhexidine, an MMP inhibitor, applied after phosphoric-acid-etching. Contralateral pairs of bonded Class I restorations in primary molars of clinical subjects were retrieved after a six-month period of intra-oral functioning and processed for transmission electron microscopy. Hybrid layers from the chlorhexidine-treated teeth exhibited normal structural integrity of the collagen network. Conversely, abnormal hybrid layers were seen in the control teeth, with progressive disintegration of the fibrillar network, to the extent that it was beyond detection by collagen staining. Self-destruction of collagen matrices occurs rapidly in resin-infiltrated dentin in vivo and may be arrested with the use of chlorhexidine as an MMP inhibitor.
Keywords: Collagenolysis; Gelatinolysis; Hybrid layer; MMPs; Primary dentin